Proses Pembentukan Kampung Tematik Di Kampung Budaya Tehyan, Kelurahan Mekarsari, Kecamatan Neglasari, Kota Tangerang - Jasmine, Rossiana; Fawzi, Indra Lestari (UI Scholars Hub, 2022)
Poverty is a problem that continues to exist in urban and rural areas. With the ‘1 RW 1 Kampung Tematik’ movement, Tangerang city government makes the thematic village an effort to improve environmental conditions while at the same time elevating the socio-economic potential of the community and ultimately alleviating poverty. Kampung Budaya Tehyan is one of the thematic villages located in RW 04, Mekarsari Village, Neglasari District, Tangerang City and it focuses on the cultural theme and potential of the minority Benteng Chinese ethnic community. This article discusses the establishment process of Kampung Budaya Tehyan together with its supporting and hindering factors. The descriptive study uses a qualitative approach with interviews, field observations, and documentation studies as forms of the data collection method. The study result shows that the establishment process of Kampung Budaya Tehyan begins as the Benteng Chinese community feel the perceived need to conserve and showcase the culture that they have preserved for hundreds of years while improving their social and economic condition. In addition, the establishment process is supported by cultural and tourism potential which is very suitable to be the village’s unique theme, and also full support from several stakeholders related to thematic village establishment in Tangerang city. However, several hindering factors such as the community’s indifference and misperception of the existence of Kampung Budaya Tehyan and the limited number of staff who can manage several activities in Kampung Budaya Tehyan also affect the slow development progress of Kampung Budaya Tehyan as a tourism destination.